Right Ventricular Damage in COVID-19: Association Between Myocardial Injury and COVID-19 - Lan, Yonghao; Liu, Wei; Zhou, Yujie (Frontiers in Cardiovascular Medicine, 2021)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2, is a global pandemic. It has resulted in considerable morbidity and mortality around the world. The respiratory system is the main system invaded by the virus involved in COVID-19. In addition to typical respiratory manifestations, a certain proportion of severe COVID-19 cases present with evidence of myocardial injury, which is associated with excessive mortality. With availability of an increasing amount of imaging data, right ventricular (RV) damage is prevalent in patients with COVID-19 and myocardial injury, while left ventricular damage is relatively rare and lacks specificity. The mechanisms of RV damage may be due to increased RV afterload and decreased RV contractility caused by various factors, such as acute respiratory distress syndrome, pulmonary thrombosis, direct viral injury, hypoxia, inflammatory response and autoimmune injury. RV dysfunction usually indicates a poor clinical outcome in patients with COVID-19. Timely and effective treatment is of vital importance to save patients' lives as well as improve prognosis. By use of echocardiography or cardiovascular magnetic resonance, doctors can find RV dilatation and dysfunction early. By illustrating the phenomenon of RV damage and its potential pathophysiological mechanisms, we will guide doctors to give timely medical treatments (e.g., anticoagulants, diuretics, cardiotonic), and device-assisted therapy (e.g., mechanical ventilation, extracorporeal membrane oxygenation) when necessary for these patients. In the paper, we examined the latest relevant studies to investigate the imaging features, potential mechanisms, and treatments of myocardial damage caused by COVID-19. RV damage may be an association between myocardial damage and lung injury in COVID-19. Early assessment of RV geometry and function will be helpful in aetiological determination and adjustment of treatment options.